Small molecules as ligands in the tuning of immune regulatory receptors - Fioretto, Laura; Ziaco, Marcello; Nuzzo, Genoveffa; Albiani, Federica; Saponaro, Marisa; Carbone, Dalila; Barra, Giusi; dell’Isola, Mario; Follero, Olimpia; Esercizio, Nunzia; Castiglia, Daniela; d’Ippolito, Giuliana; et al. (Frontiers in Immunology, 2025)
Professional antigen-presenting cells (APCs) represent a crucial link between the innate and the adaptive immune response. APCs express specific surface receptors which are primarily involved in “non-self” and/or “self” ligand recognition. Upon ligand binding, these receptors can trigger cell signalling leading to the production of pro-inflammatory cytokines, chemokines and Type 1 interferons, supporting antimicrobial and inflammatory responses. Recently, two major families of receptors, C-type lectin receptors and immunoglobulin receptors, are emerging as potential therapeutic targets to activate and modulate immune system through different intracellular signalling motifs upon binding with endogenous and exogenous ligands. The chemical characterization of the molecular determinants necessary for the receptors/ligands binding promotes the design and optimization of small molecules crucial for the comprehension of biological functions and for the therapeutic treatment of specific receptor-associated disorders. This review focuses on the description of these ligands together with their biological evaluation and their impact on the modulation of the immune response.